Development of Automatic Gas Detector System for Prevention of Fire and Life Hazards - Mann Patel; Sujal Hire; Yash Iste; Prathamesh Mogal; V E Kothawade (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The occurrence of gas leaks can have catastrophic consequences, including fires, explosions, and loss of life. To mitigate these risks, this study presents the development of an automatic gas detector system that can detect gas leaks in real-time and alert individuals in the surrounding area. The proposed system utilizes a combination of gas sensors, microcontrollers, and communication modules to detect and report gas leaks. The system’s performance was evaluated through a series of experiments, which demonstrated its ability to detect gas leaks accurately and reliably. The results of this study suggest that the proposed system can provide a reliable and efficient solution for preventing fires and life hazards caused by gas leaks.